American Family Physician (Kansas American academy of Family Physicians, 2004)
Contents: Transient ischemic attacks: Part I. Diagnosis and evalution, Part II: Treatment; Evalution and management of suspected retinal detachment; Atypical pathogens and challenges in community-acquired pneumonia; shoulder dystocia.
Keywords: Tạp chí